1987
DOI: 10.3168/jds.s0022-0302(87)80260-6
|View full text |Cite
|
Sign up to set email alerts
|

Multitrait Estimation of Genetic Parameters of Lactation Curves in Holstein Heifers

Abstract: Weekly milk yields of 1022 Holstein heifers from 61 sires were used to derive coefficients of the lactation curves using modified gamma and inverse polynomial functions. The natural logarithm of a modified gamma function was ln(yn) = ln (a) + b ln (n) + cn + u sin (x) + v cos (x), where a, b, c, u, and v are coefficients to be estimated; n is the day of lactation; and x is the day of year. Estimates of a, b, and c were combined to define persistency [-(b + 1) ln c], week of peak yield (b/c), and peak yield [a(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
5
14
0
3
Order By: Relevance
“…The low heritability estimates for lactation curve traits suggest that such traits are mainly dependent on environmental variation. The heritability estimates for parameters A, B and C are in agreement with those reported by Batra et al (1987) and Farhangfar & Rowlinson (2007). However, Farhangfar & Rowlinson (2007) and López-Ordaz et al (2009) reported estimates that are greater for Y max (0.28), T max (0.11 and 0.17) and MY305 (0.30 and 0.28).…”
Section: Genetic and Phenotypic Effectssupporting
confidence: 81%
See 1 more Smart Citation
“…The low heritability estimates for lactation curve traits suggest that such traits are mainly dependent on environmental variation. The heritability estimates for parameters A, B and C are in agreement with those reported by Batra et al (1987) and Farhangfar & Rowlinson (2007). However, Farhangfar & Rowlinson (2007) and López-Ordaz et al (2009) reported estimates that are greater for Y max (0.28), T max (0.11 and 0.17) and MY305 (0.30 and 0.28).…”
Section: Genetic and Phenotypic Effectssupporting
confidence: 81%
“…This genetic pool was subjected to some studies dealing with reproduction and production traits (Boujenane & Maty 1986, Boujenane & Aïssa 2008 and estimation of genetic parameters (Boujenane 2002), in order to improve production traits under Moroccan conditions. Furthermore, some authors have assessed the inclusion of lactation curve traits such as peak milk yield and persistency as selection criteria to improve total milk yield (Batra et al 1987). However, there are no estimates available for the genetic covariances that involve lactation curve traits in Moroccan dairy cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Los valores de heredabilidades encontrados en este trabajo fueron inferiores a los reportados en trabajos anteriores (6,8), los cuales obtuvieron valores para producción total de entre 0.34 y 0.41; para la producción en el pico de entre 0.23 y 0.30; para días al pico de entre 0.02 y 0.18, y para producción inicial de 0.1.…”
Section: Discussionunclassified
“…La cuantificación de esta variación permite realizar selección de animales para estas características. Algunos trabajos mencionan heredabilidades para las características producción inicial (b o ), días al pico, producción en el pico y producción total entre 0.08-0.1, 0.02-0.18, 0.18-0.23 y 0.30-0.41, respectivamente (6)(7)(8).…”
Section: Introductionunclassified
“…Estudos de SCHNEEBERGER (1981), FERRIS et al (1985, BATRA et al (1987) RESUMO -Os objetivos deste trabalho foram identificar as funções matemáticas que melhor se ajustam à produção de leite de vacas da raça Guzerá, avaliar os efeitos dos fatores de ambiente sobre a forma da curva de lactação e estimar parâmetros genéticos para a produção de leite e para os componentes responsáveis pela forma da curva de lactação. Foram utilizadas 1130 lactações de 583 vacas da raça Guzerá, filhas de 165 touros, com produções abrangendo o período de 1983 a 1997.…”
Section: Introductionunclassified